Oral Health-Related Quality of Life Determinants in the Elderly from a Costa Rican Day Center: Findings of a Pilot Study - Barboza-Solís, Cristina (2020)
The change in the demographic distribution of Costa Rica establishes the elderly as a public health priority. Oral health is a multidimensional indicator, which includes biological, social, and psychological dimensions. Besides using measures of morbidity and mortality, different indicators seek to approximate other subjective dimensions. There is an increasing interest in analyzing the role of quality of life on health. This study aims to identify the main determinants of Oral Health-Related Quality of Life (OHRQL) in the elderly attending a day center in the city of Desamparados (San José, Costa Rica). This is a descriptive cross-sectional study ran between 2018 and 2019. OHRQL was measured via the General / Geriatric Oral Health Assessment Index (GOHAI). As independent variables, sociodemographic, socioeconomic, morbidity, health behaviors, and drug consumption were included. Bivariate analyzes were performed using the Wilcoxon, Kruskall-Wallis, and Spearman non-parametric tests, using STATA 14. This study revealed differences in GOHAI scores according to demographic, socioeconomic, morbidity, medication, and health behaviors. Those over 80 years old, women, with higher levels of education, high income, without edentulism, with low levels of xerostomia, people without diseases, who do not take medication, who do not smoke, play sports, do not snack and who consume moderately sugars, are those that report a better OHRQL compared to their counterparts.